Acute and chronic limb ischaemia. Issue 4 (April 2016) - Budge, James; Patterson, Benjamin; Loftus, Ian
Abstract: Acute (ALI) and chronic limb ischaemic (CLI) make up a major part of the workload of vascular surgeons and carry considerable morbidity and mortality. Peripheral artery disease (PAD) is the major cause of these conditions. Diagnosis of these conditions involves proper use of imaging including duplex ultrasound, computed tomography angiography (CTA), magnetic resonance angiography (MRA), as well as invasive techniques like digital subtraction angiography (DSA). Management ranges from conservative techniques, the mainstay of management in intermittent claudication (IC), with medical optimization, through to endovascular and open revascularization techniques in CLI and ALI. Finally where no revascularization options exist, primary amputation or palliation must be considered.